VERMICOMPOST APPLICATION IMPROVING SEMIARID-GROWN CORN GREEN EAR AND GRAIN YIELDS - Silva, Paulo Sérgio Lima e (2017)
Intensive corn farming quickly depletes soil organic matter in the nutrient-poor soils of the Brazilian semiarid region. Application of vermicompost, an excellent organic fertilizer, could help solve that problem. This study evaluated the effect of applying Eisenia fetida vermicompost in the seeding furrows, at 0, 2, 4, 6, 8, and 10 Mg.ha-1 application rates, on the green ear yield and grain yield of two corn cultivars. Treatments were replicated five times with split-plots (vermicompost application rates within plots) in a completely randomized block design. The number of mature ears, number of kernels per ear (cultivar BR 106), and 100-kernel weight (cultivar AG 1051) were not affected by vermicompost application rate. However, vermicompost application increased total number and weight of unhusked and husked marketable green ears as well as grain yield. Total number of green ears was higher in cultivar BR 106 than in cultivar AG 1051. Conversely, grain yield and total ear weight and marketable weight of unhusked and husked green ears was higher in cultivar AG 1051, but responses in the latter two traits were dose-dependent.